2018
DOI: 10.1177/0391398818784275
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis during cardiopulmonary resuscitation in patients with severe metabolic acidosis

Abstract: The addition of high-efficiency hemodialysis during cardiopulmonary resuscitation may contribute to the return of spontaneous circulation in patients with severe metabolic acidosis due to intoxication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Increased cerebral blood flow means more oxygen and energy supply to the brain during CPR, which may attenuate ischemic brain injury. Furthermore, severe acidosis has been reported to not only reduce cardiac output (35,36) but also increase damage of GABAergic cells and free radical reactions in the brain, exacerbating nerve cell damage after CA (37). In the present study, our results demonstrated that the metabolic acidosis in the STD-CPR group was more severe during resuscitation, which might have resulted in more severe brain damage in the STD-CPR group compared with the AACD-CPR group.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cerebral blood flow means more oxygen and energy supply to the brain during CPR, which may attenuate ischemic brain injury. Furthermore, severe acidosis has been reported to not only reduce cardiac output (35,36) but also increase damage of GABAergic cells and free radical reactions in the brain, exacerbating nerve cell damage after CA (37). In the present study, our results demonstrated that the metabolic acidosis in the STD-CPR group was more severe during resuscitation, which might have resulted in more severe brain damage in the STD-CPR group compared with the AACD-CPR group.…”
Section: Discussionmentioning
confidence: 99%
“…Signs and symptoms frequently associated with ethylene glycol intoxication include high anion gap metabolic acidosis, high osmolar gap, AKI, neurological dysfunction, and cardiopulmonary complications including cardiac arrest [ 5 ]. Treatment involves inhibition of alcohol dehydrogenase (ADH) using fomepizole or ethanol to block toxic metabolite formation and sodium bicarbonate to correct metabolic acidosis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…69 The successful utilization of high-efficiency hemodialysis during cardiopulmonary resuscitation (CPR) in patients with severe metabolic acidosis from ethylene glycol and metformin intoxications corroborates the causeand-effect relationship between acidosis and cardiac arrest. 70 Distinguishing between acidosis as the cause, the effect, or both in cardiac arrest scenarios can be challenging in real-world practice. For instance, a case study involved a 66-year-old man undergoing orthotopic liver transplantation for alcohol-related endstage liver disease.…”
Section: Acidosismentioning
confidence: 99%
“…69 The successful utilization of high-efficiency hemodialysis during cardiopulmonary resuscitation (CPR) in patients with severe metabolic acidosis from ethylene glycol and metformin intoxications corroborates the cause-and-effect relationship between acidosis and cardiac arrest. 70…”
Section: Poca Due To Contractility Crisismentioning
confidence: 99%